The Effect of mCSCL to Improve Student Learning Outcomes - Muhammad Wahid Syaifuddin; Nugroho Arif Sudibyo (Jurnal Studi Guru dan Pembelajaran, 2021)
Mobile Computer-Supported Collaborative Learning (mCSCL) is an alternative that can be used in mobile learning. In this study, mCSCL consists of three steps. First, create groups of three to five students. Second, make learning activities starting from understanding the problem to discussion. Third, facilitating group discussions starting from one-to-one discussions to dissemination. The goal of this study was to see how mCSCL affected student learning results. The participants in this study were students from Duta Bangsa University's Informatics Engineering Study Program, which comprised of three classes totaling 90 individuals. This research is a quasi-experimental study with a one-way analysis of variance. The independent variables in this study were mCSCL, mobile learning, and e-learning based on Moodle. The results show that there are differences in learning outcomes in the number of material from the three learning models carried out. The mCSCL model is more effective than using the Mobile Learning model. Furthermore, the mobile learning model is more effective than e-learning Moodle